High-Frequency Transient Elastography Prototype to Assess Skin (Dermis) Fibrosis: A Diagnostic Study in Patients with Venous Insufficiency and Controls - Mofid, Yassine; Faleweei, Geoffroy; Chartier, Caroline; Machet, Laurent; Vierron, Emilie; Gissot, Valerie; Tauveront, Valerie; Georgescou, Gabriela; Dujardin, Paul-Armand; Machet, Marie-Christine; Kervarrec, Thibault; Patat, Frédéric; Ossant, Frederic; Maruani, Annabel (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose High-frequency transient elastography (HF-TE) is a noninvasive technique for assessing shear-wave speed and finally elasticity in thin tissue such as the skin. It has never been validated for monitoring fibrotic skin diseases. The purpose was to evaluate the potential of HF-TE to assess skin fibrosis in patients with chronic venous disorders (CVD).Materials and Methods This clinical study enrolled 48 patients at various stages of CVD and 48 paired healthy volunteers. Subjects underwent a clinical examination with an evaluation of Rodnan’s fibrosis skin score. We studied the dermis thickness measured using ultrasound (US) and elasticity measurements using cutometer and HF-TE studied according to 3 cutaneous zones positioned on the leg. The area under the receiver operating characteristic curve (AUC) was calculated to evaluate the diagnosis performance for a combined parameter (PRL) based on a logistic regression model using both elasticity and dermal thickness.Results Patients with CVD had significantly higher values of skin elasticity than healthy subjects, 134.5 kPa and 132.1 kPa vs. 91.3 kPa, respectively. The dermis thickness also increased with escalation in CVD stage for all studied zones. The PRL parameter had an AUC value of 0.79 for all zones and stages of CVD clustered. The discriminating power of PRL increased with escalation of the CVD stage; with an AUC value of up to 0.89 for evolved stages, and a sensitivity and specificity of 0.79 and 0.89, respectively.Conclusion HF-TE, coupled with a US measurement of dermis thickness, made it possible to propose a new biomarker, which proved to be a good diagnostic tool for skin fibrosis.
Keywords: chronic venous disorders; high frequency transient elastography; skin fibrosis; dermis thickness; young’s Modulus